PENGEMBANGAN BAHAN AJAR LKS (LEMBAR KERJA SISWA) BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN PEMAHAMAN SISWA DALAM OPERASI HITUNG PERKALIAN BILANGAN PECAHAN KELAS VSD - Sulaikhah Sulaikhah; Sri Utaminingsih; Sumaji Sumaji (Universitas Negeri Medan, 2022)
The results showed that the product (LKS) was contextually based with the operating material of calculating fractional numbers for elementary school V grade students using the research and development research type with the Borg and Gall Version with a research procedure using seven steps of work resulting in a contextual-based LKS teaching material development design that can improve the understanding of the operation of calculating fractional number multiplication of SDN class V students The accuracy and validation results from material experts, media and teachers show a fairly high interpretation. Obtained percentage and eligibility criteria for content 87% (very feasible), eligibility for presentation 75% (feasible), contextual assessment 81% (feasible), feasibility of graphing 79% (feasible), and language assessment 85% (worthy). Contextual-based LKS affected cognitive learning outcomes indicated by a t test significance value of 0.000 < 0.05. Gain test of 0.37 with medium criteria, percentage of student and teacher response after use of contextually based LKS is classically 90.9% with very positive criteria, student response percentage is classically 81.15% with positive criteria. The conclusion of this research is a contextual-based LKS developed for the operating material of calculating fractional numbers for elementary school V grade students in class V students is feasible and effective to use as an alternative teaching material in schools.